2015
DOI: 10.1007/s12208-015-0142-7
|View full text |Cite
|
Sign up to set email alerts
|

Does meeting BBB accountability standards affect charitable giving? A study of New York Metropolitan area charities, replicated by a US national sample

Abstract: Nonprofit organizations acquire resources from diverse sources, wherein donations play a significant role for many. To help donors and other source of public support make donative decisions, Better Business Bureaus under its Wise Giving Alliance conduct and publish review results of participating nonprofit organizations based on nationally developed criteria named as BBB STANDARDS FOR CHARITY ACCOUNTABILITY. This study assess the impact of meeting all BBB accountability criteria on the amount of public support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Sloan (2009) shows that positive ratings by the BBB Wise Giving Alliance have a significant effect on contributions received by charities (though "did not pass" ratings have not). The research by Chen (2009Chen ( , 2016 found, too, that meeting BBB standards has a positive effect on giving behavior and is associated with higher levels of public financial support. He thus recommends participating in assessment programs to increase fundraising revenues.…”
Section: Theory Of Perceived Risk -The Perspective Of Donorsmentioning
confidence: 99%
“…Sloan (2009) shows that positive ratings by the BBB Wise Giving Alliance have a significant effect on contributions received by charities (though "did not pass" ratings have not). The research by Chen (2009Chen ( , 2016 found, too, that meeting BBB standards has a positive effect on giving behavior and is associated with higher levels of public financial support. He thus recommends participating in assessment programs to increase fundraising revenues.…”
Section: Theory Of Perceived Risk -The Perspective Of Donorsmentioning
confidence: 99%